Manfaat Progressive Muscle Relaxation (PMR) sebagai intervensi keperawatan dalam meningkatkan Quality of Life (QOL) wanita kanker payudara yang menjalani kemoterapi - Anastasia Diah Larasati; Anggorowati Anggorowati; Andrew Johan (Program Studi S1 Keperawatan Universitas Ngudi Waluyo, 2019)
Based on epidemiological data, the incidence recorded globally by theInternational Agency for Research On Cancer (IARC) in 2012, as many as 43.3women had breast cancer. The patient will undergoing chemotherapy andexperience various disturbing symptoms. Various complaints can affect QOL.One of the therapies recommended by the journal Oncology Nursing is thetherapy of Progressive Muscle Relaxation (PMR).Objective: To find out the benefits of PMR as one of the nursing interventions indealing with the quality of life for women Ca. Mammae is undergoingchemotherapyThe method used in this paper is a review literature study. Databases used insource search are CINAHL, PubMed, Science Direct, and Medline. The criterionof inclusion in literature search is the year of article publishing starting in 2010until 2018, and the English full article. Search keywords are Progressive MuscleRelaxation, breast cancer, quality of life and chemotherapy. Literature analysisuses PICOT (Population, Intervention, Comparison, Outcome, and Time).Based on the analysis found 5 themes, namely the quality of life characteristicsof patients undergoing chemotherapy, PMR as a relaxation therapy, PMR as apsychological stress reduction intervention, PMR as an intervention to increasemuscle metabolism, and PMR as a pain reduction intervention.Patients who undergoing chemotherapy will experience a decrease in QOL. PMRis a recommended intervention to improve patient QOL.